How does age affect injury characteristics in young elite footballers?: a prospective cohort study of a German youth academy - Weishorn, Johannes; Jaber, Ayham; Trefzer, Raphael; Zietzschmann, Severin; Kern, Ralph; Spielmann, Jan; Renkawitz, Tobias; Bangert, Yannic (Journal of Clinical Medicine, 2023)
Background: Little is known about age-related changes in injury characteristics and burden, and existing data are inconsistent, highlighting the need for new studies on this topic. This study aimed to describe age-related injury risk, severity and burden in a German elite youth football academy. Methods: A prospective cohort study was conducted in the 2012/2013 season, reporting 109 time-loss injuries among 138 young athletes playing at an elite football academy in Germany. For the most severe injuries, the injury burden in the different age groups was considered separately. Results: Athletes missed a total of 2536 days of exposure, resulting in an overall incidence of 2.6 per 1000 h (1.7-3.0; 95% CI) and a burden of 60.6 days lost per 1000 h (40.8-80.3; 95% CI). The incidence and burden of joint sprains and muscle injuries were higher in the older age groups. Physeal injuries peaked in the U14 age group during the pubertal growth spurt. Bone injuries and contusions showed no age trend. Conclusion: Injury characteristics vary with age. The overall incidence, severity and burden of injuries increased with the age of the athletes. To ensure the optimal development of young athletes, it is important to be aware of the differences in injury susceptibility between age groups in order to implement tailored prevention programmes.